2012
DOI: 10.1111/j.1524-4741.2012.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Mastectomy Rates Among all Age Groups for Early Stage Breast Cancer: A 10-Year Study of Surgical Choice

Abstract: First-line surgical options for early stage breast cancer and ductal carcinoma in situ include breast conserving surgery or mastectomy. We analyzed factors that influence the receipt of mastectomy and resultant trends over time. Registry analysis was carried out for 21,869 women who underwent up-front surgical treatment for stage 0, I or II breast cancer between 1998 and 2007 using data from the Kentucky Cancer Registry. We examined the trend of treatment over time and assessed the probability of receiving mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
77
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 32 publications
7
77
1
1
Order By: Relevance
“…Statement and reviews of evidence from randomized trials (Abrams et al, 1995;Fisher et al, 1995), mastectomy rates declined markedly in the U.S. (Lazovich et al, 1991;Lazovich et al, 1997;Habermann et al, 2010), Canada, (Gaudette et al, 2004) European countries, (Zorzi et al, 2006), although with a more recent upturn suggested in some North American localities (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). Australian data also showed a trend away from mastectomy towards breast conserving surgery both nationally and in a number of jurisdictions (Hill et al, 1990;1994;Byrne et al, 1993;South Australian Cancer Registry, 2000;Cuncins-Hearn et al, 2006;Kricker, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Statement and reviews of evidence from randomized trials (Abrams et al, 1995;Fisher et al, 1995), mastectomy rates declined markedly in the U.S. (Lazovich et al, 1991;Lazovich et al, 1997;Habermann et al, 2010), Canada, (Gaudette et al, 2004) European countries, (Zorzi et al, 2006), although with a more recent upturn suggested in some North American localities (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). Australian data also showed a trend away from mastectomy towards breast conserving surgery both nationally and in a number of jurisdictions (Hill et al, 1990;1994;Byrne et al, 1993;South Australian Cancer Registry, 2000;Cuncins-Hearn et al, 2006;Kricker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mastectomy rates for early invasive disease vary widely within and between countries (Hill et al, 1990;1994;Lazovich et al, 1991;Byrne et al, 1993;Taylor et al, 1999;South Australian Cancer Registry, 2000;Federation European Cancer Societies, 2004;Anderson et al, 2008;Dixon and Mak, 2008;Kricker, 2011;Dragun et al, 2012a), with higher rates reported for…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations